2017
DOI: 10.1002/2016jf004151
|View full text |Cite
|
Sign up to set email alerts
|

Comment on “A Simple Model for Regolith Formation by Chemical Weathering” by Braun et al.: Contradictory Concentrations and a Tale of Two Velocities

Abstract: An intriguing model has been presented predicting that the rate of deepening of the critical zone is proportional to lateral hydraulic gradients in a hillslope's perched aquifer. Unfortunately, the model is based on assumptions that lead to a contradiction and the prediction that discharge concentrations are supersaturated with respect to weathering products. Consequently, the remainder of the paper's deductions from the model cannot be regarded as valid. A corrected version of the model implies that deepening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The Figures D1 and D2 (Supporting Information Appendix D) also contradict assumptions made about the relationship between horizontal and vertical Darcy velocities in previously published models (Braun et al ., , ). Because these assumptions are crucial for their models, the results and conclusions obtained in their work should be considered with caution as noted previously (Harman et al ., ). Note that although our model does not consider the unsaturated zone, and calculated pressure heads could thus differ from those for combined saturated–unsaturated models, our model does not predict non‐physical fluxes directed into the subsurface domain through the right boundary (Figures ).…”
Section: Weathering Without Erosionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Figures D1 and D2 (Supporting Information Appendix D) also contradict assumptions made about the relationship between horizontal and vertical Darcy velocities in previously published models (Braun et al ., , ). Because these assumptions are crucial for their models, the results and conclusions obtained in their work should be considered with caution as noted previously (Harman et al ., ). Note that although our model does not consider the unsaturated zone, and calculated pressure heads could thus differ from those for combined saturated–unsaturated models, our model does not predict non‐physical fluxes directed into the subsurface domain through the right boundary (Figures ).…”
Section: Weathering Without Erosionmentioning
confidence: 99%
“…Many reactive transport models of weatheringincluding most of our previous articles cited laterposit that solutes move by diffusion or advection in only one direction. Recently, researchers have moved beyond simulations of weathering under the condition of one-dimensional (1D) advection to consider or speculate about the importance of 2D advection (Rempe and Dietrich, 2014;Braun et al, 2016;Pandey and Rajaram, 2016;Brantley et al, 2017;Harman et al, 2017;Lebedeva and Brantley, 2018;Anderson et al, 2019;Harman and Cosans, 2019;Harman and Kim, 2019;Reis and Brantley, 2019). Here we expand on our previous models for weathering and eroding hills and consider a model describing changes in flow conditions within eroding hills that are essentially caused by geochemical reactions.…”
Section: Rationale For Our Approachmentioning
confidence: 99%
“…The Philip theory indeed delivers a net infiltration that has a term proportional to the square root of the time; thus it would be possible to generate a time-dependence for chemical weathering more or less equal to what is typically observed, while preserving the proportionality of weathering to the flow rate. This publication has been criticized by Harman et al (2017) who found that the specific flow paths envisioned by Braun et al (2016) were not realistic. Since we do not specify the flow paths in the same level of detail, we do not find this criticism compelling.…”
Section: Most Closely Related Modelmentioning
confidence: 99%
“…Other hypotheses have been put forward that emphasize the importance of hillslope hydraulics as both a driver and result of critical zone evolution. Rempe and Dietrich () and Braun, Mercier, Guillocheau, and Robin () make use of hydraulic groundwater theory to build quantitative frameworks predicting the influence of lateral flow on critical zone architecture (for a discussion of Braun et al, , see Harman, Cosans, and Putnam, ). Rempe and Dietrich's () model suggests that lateral flow through the unweathered bedrock, driven by its relief above the adjacent stream, could draw reactive water into pores (and even evacuate them when water was not available) at the upper extent of the unweathered rock, initiating weathering.…”
Section: Introductionmentioning
confidence: 99%